2004
DOI: 10.1128/aac.48.6.2101-2107.2004
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Antimicrobial Resistance among Clinical Streptococcus pneumoniae Isolates in Asia (an ANSORP Study)

Abstract: Isolates from Hong Kong showed the highest rate of ciprofloxacin resistance (11.8%), followed by isolates from Sri Lanka (9.5%), the Philippines (9.1%), and Korea (6.5%). Multilocus sequence typing showed that the spread of the Taiwan 19F clone and the Spain 23F clone could be one of the major reasons for the rapid increases in antimicrobial resistance among S. pneumoniae isolates in Asia. Data from the multinational surveillance study clearly documented distinctive increases in the prevalence rates and the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
246
3
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(285 citation statements)
references
References 30 publications
14
246
3
12
Order By: Relevance
“…6 Studies involving bacterial culture from blood have found that Streptococcus pneumoniae and Haemophilus influenzae are the most common etiological agents for pneumonia and meningitis in children with the pneumococcal serotypes 1, 6, 9, 14, 19, 23 and H. influenzae serotype b as the most prevalent causative agents. 7,8 Although official data on Hib disease in the Philippines is limited, studies have reported that the majority (∼80%) of Hib-related pneumonia and meningitis occur in the first year of life. 9,10 In view of the high global coverage of combined DTP vaccines, the addition of new antigens to existing DTP vaccines is the most effective way to achieve rapid vaccine coverage with the new antigen.…”
Section: Resultsmentioning
confidence: 99%
“…6 Studies involving bacterial culture from blood have found that Streptococcus pneumoniae and Haemophilus influenzae are the most common etiological agents for pneumonia and meningitis in children with the pneumococcal serotypes 1, 6, 9, 14, 19, 23 and H. influenzae serotype b as the most prevalent causative agents. 7,8 Although official data on Hib disease in the Philippines is limited, studies have reported that the majority (∼80%) of Hib-related pneumonia and meningitis occur in the first year of life. 9,10 In view of the high global coverage of combined DTP vaccines, the addition of new antigens to existing DTP vaccines is the most effective way to achieve rapid vaccine coverage with the new antigen.…”
Section: Resultsmentioning
confidence: 99%
“…En los menores de seis años se observó un incremento significativo en el serotipo 14 (p = 0,04) con respecto al análisis de 1993-1999 (8), pero en los serotipos 5 y 23F se observó una disminución, aunque no significativa. El serotipo 14 es el más prevalente en los menores de seis años no sólo en Colombia sino en otros países latinoamericanos como Brasil, Argentina, Chile y Uruguay (8), así como en Estados Unidos antes de la vacuna heptavalente (23), y es recuperado con menor frecuencia en países como México (8), España (21) y los países asiáticos (11). Se observaron diferencias por regiones en la frecuencia de los serotipos al compararlas con Bogotá, aunque los nueve serotipos más frecuentes fueron los mismos en los sitios analizados.…”
Section: Discussionunclassified
“…En general, los serotipos resistentes a los antibióticos en Colombia son los mismos reconocidos universalmente, pero con diferente prevalencia (31). Particular énfasis se le ha dado al estudio de la evolución de la resistencia a la penicilina, la cual, como ha ocurrido en muchas partes del mundo, se ha incrementado durante los años de vigilancia (8,11,32).…”
Section: Discussionunclassified
See 2 more Smart Citations